Entomo-Virological Surveillance and Genomic Insights into DENV-2 Genotype III Circulation in Rural Esmeraldas, Ecuador - Andrés Carrazco-Montalvo; Diana Gutiérrez-Pallo; Valentina Arévalo; Patricio Ponce; Cristina Rodríguez-Polit; Gabriela Echeverría-Garcés; Josefina Coloma; Victoria Nipaz; Varsovia Cevallos (Pathogens, 2025)
Ecuador, a tropical country with frequent dengue outbreaks, including a surge from 16,017 cases in 2022 to 61,329 in 2024, was the focus of this study. The study was conducted in Borbon, a semi-urban rural town in the Esmeraldas province. Genomic analysis, alongside entomo-virological surveillance, provides valuable insights into DENV-2 genotypes. Five pools of female Aedes aegypti mosquitoes from Borbon tested positive for DENV serotype 2 through RT-qPCR. One positive pool (CT = 16.13) was sequenced using Illumina MiSeq, and genotyping was conducted via the Dengue Typing Tool and Maximum Likelihood phylogenetic tree. The genotype assigned was III Southern Asian-American. Comparison with other genomes revealed genetic similarity to a human dengue genome sequenced in 2021, also from Esmeraldas, clustering with genomes reported across the Americas, particularly from Colombia and Venezuela. This study enhances our understanding of dengue virus epidemiology in rural areas, emphasizing the critical role of clinical case surveillance and vector monitoring in guiding evidence-based interventions.